2021
DOI: 10.1002/pd.6075
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of healthcare professionals working in prenatal diagnosis toward expanded non‐invasive prenatal testing in China

Abstract: Objectives: To investigate the knowledge, attitudes, and practices of healthcare professionals (HCPs) working in prenatal diagnosis toward expanded non-invasive prenatal testing (NIPT) in China. Methods:We conducted a national online survey among HCPs working in prenatal diagnosis, including specialists in prenatal diagnosis and foetal medicine, obstetricians and gynaecologists, nurses in obstetrics and gynaecology, obstetric ultrasound doctors, and technicians in prenatal diagnosis laboratories. A total of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A survey found that more than 80 percent of health care professionals in China engaging in prenatal diagnosis expressed support for extending NIPT to diseases other than common trisomies. The degree of knowledge was negatively correlated with the support rate 36 . Prenatal screening for sex chromosome aneuploidies raises complex ethical issues for future children, prospective parents, and clinicians 37 .…”
Section: Discussionmentioning
confidence: 94%
“…A survey found that more than 80 percent of health care professionals in China engaging in prenatal diagnosis expressed support for extending NIPT to diseases other than common trisomies. The degree of knowledge was negatively correlated with the support rate 36 . Prenatal screening for sex chromosome aneuploidies raises complex ethical issues for future children, prospective parents, and clinicians 37 .…”
Section: Discussionmentioning
confidence: 94%
“…Currently, NIPT has rapidly gained traction for screening a limited number of chromosomal diseases, including T21, T18, T13, and sex chromosome abnormalities. Although the feasibility of expanded NIPT panels for certain microdeletion syndromes, 30 such as 22q11.21 microdeletion (DiGeorge syndrome) and 5p deletion (cri du chat syndrome), has been explored, it is crucial to acknowledge that these expanded panels may miss almost half of abnormal findings. 31 Notably, for soft markers exhibiting a high incidence of chromosomal abnormalities, invasive testing is currently recommended over NIPT, as the latter lacks clinical validation for submicroscopic CNVs.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐invasive prenatal screening (NIPS) based on cell‐free DNA in maternal plasma is being expanded to include additional chromosomal abnormalities beyond chromosomes 21, 18, 13, X and Y 1,2 . These abnormalities include rare autosomal trisomies, common microdeletion/microduplication syndromes and even genome‐wide copy‐number variants (CNVs) sized over 5 Mb.…”
Section: Subgroup Genome‐wide Nips Cma Detectable Cases Residual Risk...mentioning
confidence: 99%